POPULATION STRUCTURE OF Araucaria angustifolia IN THE IGUAÇU NATIONAL PARK - Albiero Junior, Alci; Temponi, Lívia Godinho; Galvão, Franklin; Botosso, Paulo Cesar; Guimarães, Ana Tereza Bittencourt (Floresta, 2015)
Abstract The aim of this study was to analyze the population structure, regeneration and spatial distribution of Araucaria angustifolia (Bertol.) Kuntz. within a natural forest and in forest edge with agricultural monoculture. All araucaria individuals from 10 cm high were recorded in 200 plots of 10 x 10 m. 479 individuals were sampled (416 at the edge and 63 inside). Of these, 33 were females, 37 males, 49 juveniles and 360 regenerating individuals. The population structure performance was similar to standard inverted-J. Regenerating individuals had mainly the aggregate distribution pattern, while juveniles, males and females had a uniform pattern. Density of the canopy affected frequency of the individuals, where higher frequencies at higher densities were observed, indicating that regeneration of this species is more effective in shadowed environments. Due to the large number of individuals sampled in different size classes, the Iguaçu National Park is an important conservation remaining of A. angustifolia. Keyword: Density canopy; mixed temperate rain forest; spatial distribution; regeneration. Resumo Estrutura populacional de Araucaria angustifolia no Parque Nacional do Iguaçu. O objetivo do presente trabalho foi analisar a estrutura populacional, regeneração e distribuição espacial de Araucaria angustifolia (Bertol.) Kuntz no interior de uma floresta natural e na borda de uma floresta com monocultura agrícola. Todos os indivíduos de araucária a partir de 10 cm de altura foram registrados em 200 parcelas de 10 x 10 m, sendo amostrados 479 indivíduos (416 na borda e 63 no interior). Desses, 33 eram fêmeas, 37 machos, 49 juvenis e 360 regenerantes. A estrutura da população apresentou padrão semelhante ao J-invertido. Os indivíduos regenerantes apresentaram principalmente o padrão agregado de distribuição, já para os juvenis, machos e fêmeas o padrão foi uniforme. A densidade do dossel influenciou a frequência de indivíduos, sendo observadas maiores frequências em maiores densidades, indicando que a regeneração da espécie é mais efetiva em ambientes sombreados. Devido ao grande número de indivíduos amostrados em diferentes classes de tamanho, o Parque Nacional do Iguaçu representa um importante remanescente na conservação de A. angustifolia. Palavras-chave: Densidade do dossel; Floresta Ombrófila Mista; distribuição espacial; regeneração.